Family Care Work Coverage in Pensions: Mapping and Contextualizing International Variations and Developments. (12th May 2022) - Frericks, Patricia
Abstract: Old-age pensions are the major redistributive system of present-day societies. Central to current discourses on pensions and their reforms is the relevance of work as gainful employment for building up pension rights. Family care work is largely disregarded. Applying the innovative SCQual method, this article systematically quantifies and maps family care work entitlements in ten European countries at different times. The findings suggest that empirical realities and conceptual principles of European pension systems contradict the currently dominant discourses on pensions that result from empirical and theoretical limitations. Family care work entitlements are to be found in all countries, and care work currently provides rather robust entitlements to pensions in most. Since pensions in all welfare states are increasingly built up on the basis of labor-market participation, the different approaches to covering family care work in contribution-based pension systems are separately analyzed.